O Realismo Estrutural como Suporte Metafísico da Ciência - Steinle, William (Cognitio: Revista de Filosofia, 2013)
ZAHAR, Elie. Why Science Needs Metaphysics: A Plea for Structural Realism. Chicago; La Salle, Illinois: Open Court, 2008. 291 p.